간략화된 활성슬러지 모델(ASM No. 1)을 이용한 유출수 중 암모니아성 질소의 제어에 관한 연구 - 김신걸(Shin Geol Kim); 최인수(In Su Choi); 구자용(Ja Yong Koo) (Daehan hwan'gyeong gonghag hoeji, 2007)
The control of wastewater treatment has two merits; one is to regulate water quality of effluent and the other is to reduce the cost of wastewater treatment. The purpose of this study was to control the ammonium nitrogen in effluent that is known to cause eutrophication. The control was based on simplified ASM No. 1 which had 3 component materials and 8 coefficients, and the control method was as following. Firstly the ammonium concentration of inflow was measured and the optimal aeration time in effluent was determined according to simplified ASM No. 1 to be 1.0 mg/L. If ammonium concentration of effluent was not equal to 1.0 mg/L, the influent ammonium was corrected by adaptive control. These processes above were repeatedly performed. The SBR running aerobic-anoxic phase had been controlled for 1 month with this method. As a result, the ammonium concentration of the effluent showed in the range of $0.22\sim3.1$ mg/L with an average concentration of 1.1 mg/L. The adaptive control method used in this study was found very useful to control and predict the effluent concentration of ammonium. 하폐수 처리에 대한 제어는 2가지의 장점을 가지고 있다. 유출수의 수질을 제어할 수 있다는 것과 하폐수 처리 비용의 절감이 그것이다. 본 연구의 목적은 부영양화의 원인물질로 잘 알려져 있는 암모니아성 질소를 제어함을 목적으로 한다. 제어는 간략화된 활성슬러지 모델 1(ASM No. 1)에 기초하고 있으며, 제어 방법은 다음과 같다. 우선, 유입수중 암모늄 농도를 측정하고, 간략화된 활성슬러지 모델 1(ASM No. 1)에 의하여 유출수 암모늄 농도가 1.0 mg/L가 아닐 경우 유출수의 암모늄 농도가 1.0 mg/L가 되도록 최적의 포기 시간을 산정하고 결정한다. 다음단계에서 유입수의 암모늄 농도를 교정한다. 이 과정은 계속적으로 반복되었다. 이와같은 방법에 의해 호기-무산소 조건을 반복하는 SBR 반응조가 한달간 제어되었다. 다음과 같은 결과를 얻을 수 있었다. 유출수의 암모늄 농도는 $0.22\sim3.1$ mg/L 범위를 순회하였으며, 유출수 암모늄 농도의 평균값은 1.1 mg/L이었다. 본 연구에서 사용된 Adaptive control 방법은 암모늄의 유출수 농도를 제어하고 예측하는데 매우 효과적이었다.